A framework for new product selection decision using analytic network process and knowledge management - Wudhikarn R. (2014)
This paper aims to propose a new framework applying analytic network process (ANP) considering with three currently crucial perspectives; quality, environment and cost. At the same time of the ANP processes, a knowledge creation process and also knowledge evaluation method are considered for sustaining and measuring new emerging knowledge from proposed framework. This study provides a rational of this comprehensive framework and selected methods; those are ANP, eight quality dimensions of Garvin, life cycle costing (LCC), socialization, externalization, combination and internalization (SECI) model and Skandia model. All concerning methods are discussed and argued of their potential benefits and strengths delivering to the proposed framework. © (2012) Trans Tech Publications, Switzerland.